2014
DOI: 10.1515/bmt-2013-0139
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization analysis between heart rate variability and EEG activity before, during, and after epileptic seizure

Abstract: An innovative concept for synchronization analysis between heart rate (HR) components and rhythms in EEG envelopes is represented; it applies time-variant analyses to heart rate variability (HRV) and EEG, and it was tested in children with temporal lobe epilepsy (TLE). After a removal of ocular and movement-related artifacts, EEG band activity was computed by means of the frequency-selective Hilbert transform providing envelopes of frequency bands. Synchronization between HRV and EEG envelopes was quantified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
(51 reference statements)
1
13
0
Order By: Relevance
“…The analysis concept presented in figure 1 is based on and considerably advances our previous work [20]. In that study tvCOH between EEG envelopes of fixed frequency band components and the HRV was computed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis concept presented in figure 1 is based on and considerably advances our previous work [20]. In that study tvCOH between EEG envelopes of fixed frequency band components and the HRV was computed.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study [20] we demonstrated that statistically significant coherence values between the HRV's low-frequency (HRV-LF) oscillation at about 0.1 Hz and the envelope of EEG delta-activity before and after the TLE seizure occur. Significant coherence values testify significant correlative coupling (synchronization) between two oscillatory signals of the same frequency.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The data were described in [1]. 20 EEG channels were used for analysis and the HRV was computed by means of the French-Holden algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, changes of the heart rate (HR) and HR variability (HRV) are measures used most frequently to investigate the long-term and short-term alterations of the ANS in response to the type of epilepsy and to the evolution of the epileptic seizure. We have recently shown that significant synchronization between a HRV low-frequency sub-band (0.08 -0.12 Hz) and the EEG delta-envelope (1.5 -4 Hz) can be observed both in the preictal and early postictal periods of a seizure [1]. In this study the results of the time-variant coherence analysis are used in order to analyze them by means of tensor decomposition.…”
Section: Introductionmentioning
confidence: 99%